The summer of the gypsy moths - Pennypacker, Sara, 1951- (Balzer + Bray, 2012)
A foster child named Angel and twelve-year-old Stella, who are living with Stella's great-aunt Louise at the Linger Longer Cottage Colony on Cape Cod, secretly assume responsibility for the vacation rentals when Louise unexpectedly dies and the girls are afraid of being returned to the foster care system.